Association between small intestine bacterial overgrowth and psychiatric disorders - Bogielski, Bartosz; Michalczyk, Katarzyna; Głodek, Piotr; Tempka, Bartosz; Gębski, Wojciech; Stygar, Dominika (Frontiers in Endocrinology, 2024)
Small intestinal bacterial overgrowth (SIBO) is a gastrointestinal condition characterized by abnormal colonization of bacteria in the small intestine, leading to overgrowth and alteration, which is linked to gastrointestinal issues, potentially affecting neurological and mental health. Despite existing research, we still do not understand how SIBO affects tryptophan metabolism and psychiatric diseases. We investigated the literature for connections between SIBO, tryptophan metabolism disruptions, and psychiatric disorders like autism, schizophrenia, Alzheimer's, and Parkinson's diseases. We also explored the interaction between thyroid disorders and their influence on SIBO and psychiatric illnesses. PubMed and Google Scholar databases were searched using keywords and phrases, individual and in combinations, like "SIBO," "gut microbiota," "neurologic disorders," "mental disorders," "tryptophan," "dopamine," and "thyroid disease." We focused on original research and review papers that presented empirical studies conducted on animal models and human subjects published in English between February 1992 to February 2023. The initial 2 634 534 records were preliminary screened based on title and abstract and then subjected to full-text review to exclude publications with insufficient data on SIBO, lack of a psychiatric disorder component, or methodological limitations compromising the integrity of the findings. The analysis highlights the significance of the association between psychiatric disorders and SIBO, emphasizing the role of gutmicrobial diversity in mental health. We advocate for more detailed studies, including longitudinal research, to clarify the causal relationships between SIBO, gut dysbiosis, and psychiatric disorders and for an integrated approach while treating complex psychiatric conditions.